Models of freight transport system development - Baublys, Adolfas (Transport, 2009)
When modelling a transport system and evaluating the expenditure for the sustainability of its efficiency, a dynamic model was prepared for developing the capacity of freight transportation within the common transport system. The model of developing transport modes has been elaborated applying the principles of reproduction and break‐up theory.First published online: 27 Oct 2010